Karakteristik Roti Bebas Gluten Berbahan Dasar Pati Ganyong Termodifikasi - Parwiyanti Parwiyanti; Filli Pratama; Agus Wijaya; Nura Malahayati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Modified canna starch by Heat Moisture Treatment (HMT) and xanthan gum (GX) showed had potential used in the formulation of gluten-free breads. This study aimed to explore the phyiscals and sensory caharacteristics of gluten-free breads from some types of modified canna starch. The main material was some types of modified canna starch. The study was applied Completely Randomized Design with one treatment factor of starches type (HMT-GX and HMT modified canna starches, natural canna starch with and without 1.5% of xanthan gum addition, corn starch, and wheat flour). While the characteristics of bread determined include: specific volume, color, texture, ratio between height and diameter of bread, and sensory. The results showed that the best treatment based on physical and sensory characteristics was produced using HMT-GX modified canna starch. The characteristics of gluten free bread produced have a specific volume of 2.85 ± 0.017 cm3/g, color (L *, a *, b * 75.13, +9.370; +29.40, respectively), texture of 109.03 ± 7.50 gf, bread high and diameter ratio of 0.74, hedonic score for taste, color, texture and aroma respectively 5.34; 5.46; 5.56, and 5.80 repectively (range of hedonic values from 1 = very dislike to 7 = very like).